Integrated Jacobi elliptic function solutions to the (3+1)-dimensional generalized Kadomtsev–Petviashvili equation by utilizing new solutions of the elliptic equation of order six - Ahmad H. Alkasasbeh; Belal Al-Khamaiseh; Ahmad T. Ali (Partial Differential Equations in Applied Mathematics)
In this research, the generalized (3+1)-dimensional Kadomtsev–Petviashvili equation ((3+1)-GKPE) that expresses various nonlinear phenomena was studied. An extended Jacobi elliptic function expansion method (JEFEM) was developed by considering new solutions for the Jacobi elliptic equation of order six. Then the extended method was applied to the (3+1)-GKPE, where new exact Jacobi elliptic function solutions were obtained. This equation is of particular interest as it required a special transformation in order to apply the JEFEM. Moreover, some of the solutions are shown graphically.